2018
DOI: 10.1002/slct.201802802
|View full text |Cite
|
Sign up to set email alerts
|

Selective High Binding Affinity of Azacyanines to polyd(A) polyd(T)⋅polyd(T) Triplex: The Effect of Chain Length and Branching on Stabilization, Selectivity and Affinity

Abstract: Triplex nucleic acid structures receive considerable attention due to their possible role in anti-gene therapy, several diseases as Friedreich's ataxia and Deoxyribonucleic acid (DNA) based nano-structures. The modulation of triplex formation and its stabilization using small molecules is one way to enhance their utility in such applications. Here, we synthesized five new Azacyanines (Azaethyl (2 b), Azapropyl (2 c), Azaisopropyl (2 d), Azabutyl (2 e), Azaisobutyl (2 f)) and assessed their affinity and selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Accordingly, during the last years, the major focus of our research group has been the investigation of the interactions of azacyanines with different nucleic acid structures. ,,, Among the azacyanines investigated, only 2 of them named azacyanine4 (Aza4) and azacyanine5 (Aza5) were benzothiazole derivatives, and both of them were found to be binding to the human telomeric sequence tel24 and poly­(A) with high affinity. , They were also recently evaluated for their potential as topoisomerase II inhibitors . However, one downside of the azacyanine synthesis via the previously reported method was the low yields.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, during the last years, the major focus of our research group has been the investigation of the interactions of azacyanines with different nucleic acid structures. ,,, Among the azacyanines investigated, only 2 of them named azacyanine4 (Aza4) and azacyanine5 (Aza5) were benzothiazole derivatives, and both of them were found to be binding to the human telomeric sequence tel24 and poly­(A) with high affinity. , They were also recently evaluated for their potential as topoisomerase II inhibitors . However, one downside of the azacyanine synthesis via the previously reported method was the low yields.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of azacyanines with tel24 were first investigated using UV-Vis and circular dichroism (CD) spectroscopy in order to quickly survey and confirm the presence of interactions between the azacyanines and tel24. Such a survey also reveals changes in the secondary structure of tel24 upon azacyanine binding and the effect of azacyanine structure on tel24 binding [25,[28][29][30][31][32][33][34][35][36][37]. Our previous structural studies using NMR have shown that one azamethyl was binding to one tel24 G-quadruplex structure between the top quartet and the A-T base pairing in the loop region.…”
Section: Determination Of Binding Using Uv-vis and CD Spectroscopymentioning
confidence: 92%
“…Based on all these reported studies and our knowledge on azamethyl, we were inspired to explore a series of azacyanine compounds as potential G-quadruplex stabilizing compounds with the hope of finding a better candidate than azamethyl and understanding the effect of molecular structure on molecular recognition. In the present study, we evaluated the interactions of benzimidazole derivatives, differing from azamethyl in alkyl chain length and branching, with tel24 using UV-Vis, fluorescence, and CD spectroscopy and tried to reveal the effect of molecular structure on G-quadruplex binding [37]. To the best of our knowledge, this is a unique study revealing the effect of chain length and branching on G-quadruplex recognition.…”
Section: Introductionmentioning
confidence: 99%